New record of common Banded Peacock Papilio crino in Seshachalam Biosphere Reserve, Eastern Ghats, Andhra Pradesh, India - M, Bubesh Guptha; PV, Chalapathi Rao; D, Srinivas Reddy; SRSC, Sekhar Maddala; P, Madhu Babu (Journal of Research in Biology, 2012)
The Common Banded Peacock is a member of the family Papilionidae. They accomplish pollination, a key stone ecological process in natural sustainability throughout the world. Preliminary survey was conducted to identify areas with large population of butterflies. Six locations were selected which were visited every week from August 2011 to January 2012. Mostly photographic documentation was done, we sighted Common Banded Peacock Papilio crino species near the (CBET) complex Mamandur, Talakona, Balapalli and Tirumala of Chittoor District, Andhra Pradesh. This species is very rare in Eastern Ghats. During the time of sighting, it was sunny, and few of the recorded places are mud puddle. We recommend further studies in this species in Eastern Ghats at the earliest opportunity. Also we insist on the protection of habitat is an important aspect in the conservation of such species.